2012
DOI: 10.1038/nature11726
|View full text |Cite
|
Sign up to set email alerts
|

Activated GTPase movement on an RNA scaffold drives co-translational protein targeting

Abstract: Roughly one third of the proteome is initially destined for the eukaryotic endoplasmic reticulum or the bacterial plasma membrane1. The proper localization of these proteins is mediated by a universally conserved protein targeting machinery, the signal recognition particle (SRP), which recognizes ribosomes carrying signal sequences2–4 and, via interactions with the SRP receptor5,6, delivers them to the protein translocation machinery on the target membrane7. The SRP is an ancient ribonucleoprotein particle con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
89
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(103 citation statements)
references
References 38 publications
7
89
0
2
Order By: Relevance
“…S4C), confirming Ffh-FtsY NG domain flexibility. Our finding is consistent with the observation that targeting complexes formed with mutant FtsY(A335W), which blocks the rearrangement from the closed to the activated state, are incapable of docking to the distal site of 4.5S RNA in single-molecule FRET experiments (31). Instead, the closed complex appears to adopt intermediate states where the NG domains are found in positions ranging from the RNA tetraloop to the RNA distal end (Fig.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…S4C), confirming Ffh-FtsY NG domain flexibility. Our finding is consistent with the observation that targeting complexes formed with mutant FtsY(A335W), which blocks the rearrangement from the closed to the activated state, are incapable of docking to the distal site of 4.5S RNA in single-molecule FRET experiments (31). Instead, the closed complex appears to adopt intermediate states where the NG domains are found in positions ranging from the RNA tetraloop to the RNA distal end (Fig.…”
Section: Resultssupporting
confidence: 80%
“…Instead, the closed complex appears to adopt intermediate states where the NG domains are found in positions ranging from the RNA tetraloop to the RNA distal end (Fig. 2D) (31).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We now analyze the microsecond timescale MD trajectories in the context of a recent study by Shen et al (16), which used single molecule FRET experiments to monitor the SRP conformational dynamics. This experimental study labeled the SRP RNA distal end and NG domain and found that the SRP samples both a low efficiency and a high efficiency FRET state, with differences in FRET efficiency that correspond to distance changes of ϳ10 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Both structural (12)(13)(14)(15)(16)(17)(18)(19)(20)(21) and biochemical work (22)(23)(24) suggest that the SRP exhibits multiple stable conformations that are important for protein targeting. The conserved functional core of the SRP (Fig.…”
mentioning
confidence: 99%